2014
DOI: 10.5152/tud.2014.61587
|View full text |Cite
|
Sign up to set email alerts
|

Montelukast prevents testes against ischemia-reperfusion injury through suppression of iNOS expression

Abstract: Objective: To elucidate the mechanism of a possible protective effect of montelukast against testicular ischemia/reperfusion (I/R) injury. Material and methods:Fifty-one adult male Wistar-Albino rats were randomly assigned into 6 groups; sham + saline (S), sham + montelukast (M), I/R + S, I/R + S 30', I/R + M and I/R + M 30'. Saline or montelukast (10 mg/kg) was intraperitoneally administered 30 minutes prior to (S 30', M 30') and during detorsion (I/R + S, I/R + M) in the I/R groups. The I/R groups underwent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 22 publications
1
6
0
2
Order By: Relevance
“…This finding indicates that our experimental results are consistent with those in the literature. Aside from MDA, torsion-detorsion was reported to cause a significant increase in MPO activity in tissue [ 25 ]. I/R is a pathologic process that expands with inflammation [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…This finding indicates that our experimental results are consistent with those in the literature. Aside from MDA, torsion-detorsion was reported to cause a significant increase in MPO activity in tissue [ 25 ]. I/R is a pathologic process that expands with inflammation [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…Evaluation was made at ×40 microscope magnification and scoring was accepted as 0 = normal, 1 = mild effect, 2 = moderate effect, and 3 = severe effect (Table 1). [10] Biochemical Analyses…”
Section: Histopathological Analysesmentioning
confidence: 99%
“…It has been reported that it protects the kidney and bladder from ischemia/reperfusion damage, and that this molecule is beneficial in ethanol-induced mucosa injury, multi-organ failure due to sepsis, colitis, and testis torsion. [5][6][7][8][9] In addition, the use of various pharmacological and immunological agents has been suggested to decrease or avoid reperfusion injury. However, there has been no appropriately designed study regarding the effect of Montelukast on tourniquet use models.…”
Section: Introductionmentioning
confidence: 99%
“…alt grubu). Çalışma-mızda montelukast'ın uygulanan dozu daha önce yapılan çalışmalara dayanmaktadır (18,19). Diğer altgruplara ise montelukast yerine %0.9'luk SF, 100 µL/kg ile 10 günlük sü-re ile verildi.…”
Section: İlaç Tedavileriunclassified